Predrawn prehospital medications are microbiologically safe for up to 48 hours. Issue 12 (20th October 2018) - Soeyland, Torgrim; Garner, Alan; Vidler, Sam; Gutierrez, Cristian Humberto; Foster, Arnold; Kitcher, Jane
Abstract : Background: Prehospital medical teams are commonly required to administer a range of medications for urgent stabilisation and treatment. The safe preparation of medications during resuscitation requires attention, time and resources, and can be a source of medication error. In our two road and HEMS (Helicopter Emergency Medical Service) prehospital services, medication errors are mitigated by predrawing commonly used medications to set concentrations daily (Hunter Retrieval Service, HRS) or second-daily (CareFlight Sydney, CFS). However, there are no published data confirming that such practice is microbiologically safe. Methods: A convenience sample of 299 predrawn medication syringes with syringe dwell times up to 48 hours were collected at the end of their operational deployment. Predrawn medication syringes collected for culture were ketamine, midazolam, fentanyl, thiopentone, rocuronium, suxamethonium, metaraminol and normal saline. The samples were incubated and cultured at a tertiary hospital pathology laboratory using best-practice methodology for non-tissue samples. The samples were collected from June 2017 to February 2018. Results: The mean dwell times ranged from 30.7 hours (fentanyl at HRS) to 48.5 hours (rocuronium at CFS). None of the 299 cultured samples yielded significant micro-organisms. One sample of suxamethonium with a syringe dwell time of 34 hours grew Bacillus cereus but was likely a contaminant introduced during sample collection. Conclusion: Predrawing of the eight studied medications for urgent prehospital procedures appears to be a microbiologically safe practice with syringe dwell times up to 48 hours.